Есть ответ 👍

Спростіть вираз!
до іть будь ласка.

160
463
Посмотреть ответы 3

Ответы на вопрос:

Nastenkapu
4,5(30 оценок)

Применяем формулы сокращённого умножения:

\bf x^2-y^2=(x-y)(x+y)\ ,\ \ \ x^2+2xy+y^2=(x+y)^2

\displaystyle \Big(\frac{2cb}{c^2-b^2}+\frac{c-b}{2c+2b}\Big)\cdot \frac{14c}{c+b}+\frac{7b}{b-c}==\Big(\frac{2cb}{(c-b)(c+b)}+\frac{c-b}{2(c+b)}\Big)\cdot \frac{14c}{c+b}-\frac{7b}{c-b}==\frac{4cb+(c-b)^2}{2(c-b)(c+b)}\cdot \frac{14c}{c+b}-\frac{7b}{c-b}=\frac{4cb+c^2-2cb+b^2}{2(c-b)(c+b)}\cdot \frac{14c}{c+b}-\frac{7b}{c-b}==\frac{c^2+2cb+b^2}{2(c-b)(c+b)}\cdot \frac{14c}{c+b}-\frac{7b}{c-b}=\frac{(c+b)^2\cdot 14c}{2(c-b)(c+b)^2}-\frac{7b}{c-b}=  

\displaystyle =\frac{7c}{c-b}-\frac{7b}{c-b}=\frac{7c-7b}{c-b}=\frac{7(c-b)}{c-b}=7      

GenaGenaGena1
4,4(67 оценок)

Вітаю .

Відповідь: 7

Пояснення: фото.


Спростіть вираз!до іть будь ласка.
artem24322004
4,8(73 оценок)

7с²-с-с³+7=7(с²+1)-с(с²+1)=(с²+1)(7-с); 16ав²+5в²с+10с³+32ас²=16а(в²+2с²)+5с(в²+2с²)=(в+2с²)(16а+5с); 40а³вс+21вс-56ас²-15а²в²=8ас(5а²в-7с)-3в(5а²в-7с)=(5а²в-7с)(8ас-3в); ах²-ау-вх²+су+ву- сх²=а(х²-у)-в(х-у)-с(х²-у)=(х²-у)(а-в-с); ах-2а-3х+6=а(х-2)-3(х-2)=(х-2)(а-3)=(3,5-2)(1,5-3)=1,5×(-1,5)=-2,25

Популярно: Алгебра